Towards the recovery of a sense of self: An interpretative phenomenological analysis of patients' experience of body-oriented psychotherapy for schizophrenia. (4th March 2019) - Galbusera, Laura; Fellin, Lisa; Fuchs, Thomas
Abstract: Objective: Increasing evidence supports the efficacy of body-oriented psychotherapy (BPT) for schizophrenia. Yet, so far no research has investigated outcome in relation to therapy process: Why and how BPT is effective. In this study, we qualitatively explore participants' experience of a manualized BPT for schizophrenia to shed light on the process of therapeutic change. Method: We conducted in-depth interviews with 6 participants who completed a 10-week BPT group intervention. Interviews explored participants' experience of change and helpful aspects of therapy and were analysed using interpretative phenomenological analysis. Findings: We identified six master themes across the interviews: (i) Being a whole: body-mind connection; (ii) Being agentic and being able; (iii) Being unique and worthy: Being accepted for who one is; (iv) Changing interactions: Engaging in authentic interpersonal contact; (v) Being part of a group: Feeling integrated; and (vi) Hope and investing in the future. Conclusion: We discuss the clinical implications for each theme and bring the findings together by describing therapeutic change in schizophrenia as a recovery of sense of self at different but interlocked levels. Moreover, we put forward recommendations for both specific and common factors for schizophrenia therapy. Clinical or methodological significance of this article: The clinical significance of this study is twofold. On the one hand, the findings of this analysis might inform the theory and practice of BPT and might directly feedback into a further development of the manual guidelines. On the other hand, common helpful factors have been identified thatmight also be relevant for the more general clinical practice concerning patients with schizophrenia. Here, we summarize our key messages for the clinical practitioner emerging from the findings: The inclusion of bodily aspects and a focus on pre-reflective experience in psychotherapy can help persons with schizophrenia recover the sense of being a body-mind unity. Empowering persons with schizophrenia, instead of instructing them, seems to foster a sense of agency and self-confidence, which are crucial to the recovery process. A twofold therapeutic stance characterized by openness towards the other and authenticity was experienced by patients as facilitating the rapport building. This might help persons with schizophrenia engage in the relation. Social inclusion might enhance therapeutic change and recovery in schizophrenia. Group therapy might be helpful for fostering a feeling of social belonging, but the inclusion in the wider social and community context remains a critical issue. The experience of joyful moments in psychotherapy might positively contribute to therapeutic change in that it fosters a sense of hope for the future. Overall our paper contributes to the literature aiming at expanding the range of therapeutic modalities, focussing on the creation and use of mixed models of therapy within and beyond talking practices.